Unveiling Insights in the IoT Sector: Harnessing Power BI for Data Mining and Visualization - Shairy, Er.; Gourav, Er. (Journal of Advanced Research in Information Technology, Systems and Management; Vol 8 No 1 (2024): Journal of Advanced Research in Information Technology, Systems and Management, 2024)
This exploratory investigation delves into a tool utilized for data mining with robust data visualization capabilities. The tool has the potential to transform ordinary data into sophisticated representations and engaging reports. To achieve the most comprehensible, efficient, effective, and accurate information visualization, various methods of data gathering, storing, processing, analysis, and real-time visualization are essential. The article conducts a comparative exploration of data mining, Power BI, highlighting their features, benefits, drawbacks, and their application in visualizing data within the IoT industry. This analysis aims to empower organizations to optimize their data, enabling data-driven decision-making and gaining a competitive edge in today's data-centric economy. Fundamentally, this exploration aims to decode the complexities surrounding the utilization of data mining tools and Power BI for optimal data visualization within the IoT domain. A comprehensive understanding of their nuanced features and potential pitfalls empowers businesses to strategically harness these capabilities, positioning themselves as pioneers in leveraging data for innovation.